2012
DOI: 10.1093/bja/aes226
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for reintubation in the post-anaesthetic care unit: a case–control study

Abstract: Editor's key points † This study investigates the risk factors for reintubation in post-anaesthetic care units related to anaesthetic processes. † Risk factors were age ,1 yr, chronic pulmonary disease, preoperative hypoalbuminaemia and renal insufficiency, head and neck surgery, airway surgery, cardiothoracic surgery, cardiac catheterization, emergency case, duration of operation more than 3 h, ASA physical status III, and the use of certain neuromuscular blocking agents. Background. Risk factors for reintuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 18 publications
6
47
2
Order By: Relevance
“…Recent work has shown that procedures lasting more than 3 hours and patients with higher American Society of Anesthesiologists scores are at greater risk for early postoperative intubation. 19 These findings have been confirmed in the general surgical patient population, and anesthesia time frequently emerges as an independent predictor of postoperative respiratory morbidity. 20 Both American Society of Anesthesiologists score and operative time are key risk factors identified in this study that are associated with postoperative respiratory failure.…”
Section: Discussionmentioning
confidence: 77%
“…Recent work has shown that procedures lasting more than 3 hours and patients with higher American Society of Anesthesiologists scores are at greater risk for early postoperative intubation. 19 These findings have been confirmed in the general surgical patient population, and anesthesia time frequently emerges as an independent predictor of postoperative respiratory morbidity. 20 Both American Society of Anesthesiologists score and operative time are key risk factors identified in this study that are associated with postoperative respiratory failure.…”
Section: Discussionmentioning
confidence: 77%
“…26,27 In this study, American Society of Anesthesiologists physical status served as a significant predictor of postoperative respiratory morbidity (OR, 27.2; p = 0.019). This finding is critical because this appeared to be the only reliable preoperative clinical variable predictive of respiratory morbidity.…”
Section: Discussionmentioning
confidence: 62%
“…UAO in combination with reintubation occurred mostly during 60-180 minutes of anesthesia when the operation was finished and the airway device was taken out. The main risk factors were age < 1 years and airway surgery, a result supported by Ing et al [22] and Rujirojindakul et al [23] Anesthesia-related risk factors could not be determined because of the low number (23) of events.…”
Section: Discussionmentioning
confidence: 88%